Leadership competency - Abdul Kadir, Adibah; Salleh, Siti Hasliah; Johar, Sarawati; Mohd Rosli, Nur Amalina; Ismail, Fadillah (Penerbit Uthm, 2019)
Leadership is a procedure by which an individual impacts other to achieve a target and coordinates the association such that makes it increasingly firm and cognizant (Sharma & Jain, 2013). This definition is like Northouse's (2007) definition — Leadership is a procedure whereby an individual impact a gathering of people to accomplish a shared objective.